2007
DOI: 10.1007/s11104-006-9172-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of permanent raised bed planting and residue management on physical and chemical soil quality in rain fed maize/wheat systems

Abstract: Densely populated, intensively cropped highland areas in the tropics and subtropics are prone to erosion and declining soil fertility, making agriculture unsustainable. Conservation agriculture in its version of permanent raised bed planting with crop residue retention has been proposed as an alternative wheat production system for this agro-ecological zone. A five years field experiment comparing permanent and tilled raised beds with different residue management under rainfed conditions was started at El Batá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
145
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 46 publications
14
145
0
5
Order By: Relevance
“…Moreover, the chelating of these nutrients with organic matter in non-disturbed soil leads the improvement of soil nutrient status in different soil depths (Borie et al, 2006;Singh et al, 2014) and thus causes enhancement of soil NPK status. The similar findings of enhancement in available nutrients due to CA practices in soil were also reported by Graham et al, 2002;Borie et al, 2006 andWang et al, 2008 for N;Malhi et al, 2011for P and Du Preez et al, 2001and Govaerts et al, 2007 for K. The enhancement in available NPK status due to ZT and PB practices was also reported by Parihar et al, 2011. Most research reported that tillage practices does not affect extractable Ca and Mg levels of soil (Govaerts et al, 2007;Duiker and Beegle, 2006) primerily in the condition where CEC is associated with clay particles (Duiker and Beegle, 2006).…”
Section: Nutrient Dynamicssupporting
confidence: 79%
See 3 more Smart Citations
“…Moreover, the chelating of these nutrients with organic matter in non-disturbed soil leads the improvement of soil nutrient status in different soil depths (Borie et al, 2006;Singh et al, 2014) and thus causes enhancement of soil NPK status. The similar findings of enhancement in available nutrients due to CA practices in soil were also reported by Graham et al, 2002;Borie et al, 2006 andWang et al, 2008 for N;Malhi et al, 2011for P and Du Preez et al, 2001and Govaerts et al, 2007 for K. The enhancement in available NPK status due to ZT and PB practices was also reported by Parihar et al, 2011. Most research reported that tillage practices does not affect extractable Ca and Mg levels of soil (Govaerts et al, 2007;Duiker and Beegle, 2006) primerily in the condition where CEC is associated with clay particles (Duiker and Beegle, 2006).…”
Section: Nutrient Dynamicssupporting
confidence: 79%
“…According to Govaerts et al, 2007 PB had 1.65 and 1.43 times higher concentration of K in the 0-5 cm and 5-20 cm respectively, than CT. Ismail et al, 1994 also reported higher extractable K levels at the soil surface with ZT as tillage intensity decreased. Du Preez et al, 2001 observed increased levels of K in ZT compared to CT, but this effect declined with depth.…”
Section: Nutrient Dynamicsmentioning
confidence: 86%
See 2 more Smart Citations
“…During the vegetation period when the main grown crop does not protect the soil surface from the effects of intense rainfall, we can use protective functions of intercrops and crop residues left on the soil surface (Novák et al 2011) or mulch applied to the soil surface. Mulching in this manner can influence the physical and chemical properties of the soil (Govaerts et al 2007) and improve soil nitrogen availability, which supports plant growth (Fang et al 2011).…”
mentioning
confidence: 99%